The international law violations in the Russian special military operation in Ukraine case and the international community's efforts to protect - Ed. Daran, Driss; Elhajraoui, Fatima Ezzohra; Al Ajlani, Riad (Research Journal in Advanced Humanities, 2026)
The Russian incursion into Ukraine represents the foremost challenge to the post-1945 international legal framework, raising essential questions regarding sovereignty, the prohibition of force, and the effectiveness of international institutions. Russia has attempted to justify its conduct by claiming self-defence and alleging genocide in Donbas; however, this analysis demonstrates that these assertions are inconsistent with the UN Charter, the Genocide Convention, and customary international law. The article employs a normative legal framework to examine international treaties, judicial rulings, and academic discussions to assess the legality of Russia's activities and the adequacy of responses from the UN, the International Criminal Court, and the International Court of Justice. The findings indicate a dual crisis: the collapse of the universal accord on the prohibition of aggression and the incapacity to execute it due to power politics. The study situates the Ukraine conflict within the broader discussion of humanitarian intervention, Responsibility to Protect (R2P), and institutional reform, thereby enriching academic discourse on the resilience of the international legal order and the potential for accountability concerning great-power violations.